1999
DOI: 10.1115/1.2825966
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Property Variations on Natural Convection in a Square Enclosure

Abstract: Natural convection in a square enclosure with heated vertical walls and temperature-dependent conductivity and viscosity was simulated for Prandtl numbers ranging from 0.01 to 1.0 and Ra ≤ 106. Although the variable properties produced observable changes in the the temperatures and velocities, the overall heat transfer, as represented by the Nusselt number, was found to be unaffected and was accurately correlated in terms of the Rayleigh and Prandtl numbers using Nu=0.185Ra00.278Pr00.089 with properties evalua… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
24
0
2

Year Published

2008
2008
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 55 publications
(26 citation statements)
references
References 8 publications
0
24
0
2
Order By: Relevance
“…Additionally, the geometry has many applications in different industrial techniques and equipments such as solar collectors, food preservation, compact heat exchangers, and electronic cooling systems among other practical applications. As a consequence of these applications, a thorough literature exists in this field of study especially in the case of Newtonian fluids [1][2][3][4].…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, the geometry has many applications in different industrial techniques and equipments such as solar collectors, food preservation, compact heat exchangers, and electronic cooling systems among other practical applications. As a consequence of these applications, a thorough literature exists in this field of study especially in the case of Newtonian fluids [1][2][3][4].…”
Section: Introductionmentioning
confidence: 99%
“…El modelo matemático considera las ecuaciones de continuidad, momentum (Navier-Stokes), energía y masa para un fluido incompresible de densidad , viscosidad dinámica , conductividad k, difusividad D y afectado por la fuerza gravitacional g como mostrado en las ecuaciones (1)(2)(3)(4). Para el caso bidimensional, el modelo expresado por las ecuaciones (1) a (5) para un flujo transitorio bidimensional (u=(u , v)) en el plano XY (Y orientado en -g) de un fluido incompresible ( =cte.…”
Section: Dominio Fluidounclassified
“…En [1] se desarrollan aplicaciones donde se considera a la temperatura dependiente de la conductividad y la viscosidad. Otros investigadores han desarrollado modelos capaces de calcular la convección libre sobre un medio poroso en una cavidad inclinada [2].…”
Section: Introductionunclassified
“…Other articles on the topic published after 1988 show a relatively big interest in the studies of convective phenomena in cavities heated from below and cooled with different kinds of boundary conditions [3]- [5]. Towards effect of fluid properties on heat transfer, Emery and Lee [6] studied the effect of fluid property variations on the natural convection in a square enclosure with different boundary conditions on the sidewalls. A comparison of the results for a variable fluid property with those of a constant property showed that, although the fluid flow and temperature fields seem to be different, the overall heat transfer is unaffected.…”
Section: Introductionmentioning
confidence: 99%